Burning mouth syndrome - a burning enigma Sindrom pekućih usta - goruća enigma - Andabak Rogulj, Ana; Lončar Brzak, Božana; Vučićević-Boras, Vanja; Vidović Juras, Danica; Škrinjar, Ivana (2021)
Burning Mouth Syndrome (BMS) is a chronic pain condition characterized by an intraoral burning sensation and an absence of oral mucosal lesions and disturbances in laboratory findings. Burning symptoms usually affect the anterior two-thirds of the tongue, its lateral borders, hard palate and labial mucosa, but other oral cavity sites may also be affected. Taste alterations and a decrease in the salivary flow rate frequently accompany the burning symptoms. This condition mostly affects peri- and postmenopausal women. To date, the etiology of BMS remains unclear. This unknown etiology means that no appropriate treatment is currently available. A large number of the treatments and medications have been tried for BMS, but treatment management remains unsatisfactory in some patients. The purpose of this article is to present current knowledge on the treatment of BMS.
Sindrom pekućih usta (SPU) kronično je bolno stanje koje je karakterizirano osjećajem žarenja u usnoj šupljini bez vidljivih promjena na sluznici i poremećaja u laboratorijskim nalazima. Simptomi žarenja obično zahvaćaju prednje 2/3 trećine i lateralne površine jezika, tvrdo nepce, labijalnu sluznicu, ali može biti zahvaćena bilo koja regija u usnoj šupljini. Simptomi žarenja obično su praćeni promjenom osjeta okusa te smanjenim lučenjem sline. Ovo stanje najviše pogađa žene u peri- i postmenopauzi. S obzirom na to da je etiologija SPU-a nepoznata, ne postoji niti odgovarajuće liječenje. Dostupno je više različitih terapija i lijekova za SPU, međutim, liječenje kod pojedinih pacijenata i dalje je bezuspješno. Svrha ovog rada je prikazati trenutno znanje o liječenju SPU-a.
Bibliografija: 110 jed.
Abstract ; Sažetak.
Keywords: Sindrom pekućih usta -- Usna šupljina -- Liječenje -- Stomatodinija -- Stomatopiroza